2006
DOI: 10.1021/jp062123x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Titanium Nanoparticles Created by Laser Irradiation under Liquid Environments

Abstract: The results of studies of the formation of various titanium-based nanoparticles by laser ablation of a titanium rod in liquid environments comprised of water, ethanol, 2-propanol, and n-hexane are reported. The effect of fluence on nanoparticle characteristics was studied by ablation with a 532 nm Nd:YAG operating at 10 Hz, showing that mean particle size and the size distribution increase with increasing laser intensity. The solvent plays a crucial role in the nature of the nanoparticles, as solvent component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 42 publications
4
51
0
Order By: Relevance
“…Several previous workers have developed NPs of silver, gold, bismuth, etc. through this method and have studied the effects of laser power variation on the size of nanoparticles [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous workers have developed NPs of silver, gold, bismuth, etc. through this method and have studied the effects of laser power variation on the size of nanoparticles [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Golightly and Castleman reported that oxygen vacancy defect concentration is higher in larger sized LA-PLA produced TiO 2-d NPs and for a single spherical NP, oxygen vacancy concentration increases from the surface to the centre. 26 Larger volumes in bigger sized TiO 2-d NPs correspond for higher density of oxygen vacancies, and each vacancy in volume corresponds to a larger number of neighboring Ti atoms as compared to those on the surface, which results for higher degree of ferromagnetism into larger sized TiO 2-d NPs. Additionally, oxygen vacancies inside the volume may get substituted by Ti þ3 ions with one unpaired 3d electrons that induce local magnetic moments on neighboring Ti atoms.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, its corrosion resistance and biocompatibility with living tissues have made titanium essential for medical implants. Nanostructured materials based on titanium exhibit desirable mechanical properties [2], as well as high reactivity to oxygen [3,4]. Furthermore, the physical properties of titanium nanowires strongly depend on their atomic configuration.…”
Section: Introductionmentioning
confidence: 99%